Analysis of Factors Influencing Contractor Profit and Loss in Construction Projects: A Case Study of the Boemi Oemmi Luxury Kost Garut Development - Siti Patimah Adawiah; Era Agita Kabdiyono (Asosiasi Dosen Muda Indonesia, 2026)
Construction projects often face financial challenges that can lead to contractor profits or losses during project implementation. Factors such as labor productivity, material availability, equipment management, financial conditions, and field conditions may significantly affect contractor financial performance. Therefore, identifying these factors is important to improve project management and reduce financial risks. Objective: This study aims to analyze the factors influencing contractor profits and losses in the Boemi Oemmi Luxury Kost Garut construction project and to identify the most dominant factors as well as the actions implemented to address these factors. Method: This research employed a quantitative descriptive approach. Data were collected through questionnaires distributed to respondents involved in the construction project, including contractors, consultants, and project owners. The sampling technique used was purposive sampling. The collected data were analyzed using descriptive statistical methods, including mean value analysis and the Relative Importance Index, to determine the ranking of factors influencing contractor profits and losses. Findings: The results show that labor factors are the most dominant factor influencing contractor profits and losses in the Boemi Oemmi Luxury Kost Garut development project, while equipment factors have the lowest influence. In terms of the implementation of actions to address these factors, material-related issues were found to be the most highly applied factor, whereas weather-related factors were the least applied. Implications: The findings of this study provide practical implications for construction project stakeholders by emphasizing the importance of improving workforce productivity, strengthening material procurement planning, and enhancing project management strategies to minimize financial risks and improve contractor profitability. Originality: The originality of this study lies in its empirical analysis of contractor profit and loss factors within a specific construction project context using a structured ranking approach through the Relative Importance Index, which provides a systematic evaluation of factors influencing contractor financial performance.